2024
DOI: 10.1007/s13300-024-01550-5
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 Inhibitors – The New Standard of Care for Cardiovascular, Renal and Metabolic Protection in Type 2 Diabetes: A Narrative Review

Samuel Seidu,
Vicki Alabraba,
Sarah Davies
et al.

Abstract: A substantial evidence base supports the use of sodium-glucose cotransporter-2 inhibitors (SGLT2is) in the treatment of type 2 diabetes mellitus (T2DM). This class of medicines has demonstrated important benefits that extend beyond glucose-lowering efficacy to protective mechanisms capable of slowing or preventing the onset of long-term cardiovascular, renal and metabolic (CVRM) complications, making their use highly applicable for organ protection and the maintenance of long-term health outcomes. SGLT2is have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…Moreover, other studies revealed, that GPR146 may be important in vascular remodelling, along with adipose tissue development and metabolism [ 4 , 5 ]. SGLT2 inhibitors (SGLT2i) are routinely prescribed drugs to T2DM patients with cardiovascular disease, though theirs cardioprotective effects are not fully elucidated [ 6 ]. Hypotheses include the beneficial impact of decreased volemic load due to iSGLT2, anti-inflammatory properties or a direct influence of SGLT2i on cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other studies revealed, that GPR146 may be important in vascular remodelling, along with adipose tissue development and metabolism [ 4 , 5 ]. SGLT2 inhibitors (SGLT2i) are routinely prescribed drugs to T2DM patients with cardiovascular disease, though theirs cardioprotective effects are not fully elucidated [ 6 ]. Hypotheses include the beneficial impact of decreased volemic load due to iSGLT2, anti-inflammatory properties or a direct influence of SGLT2i on cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%